2020
DOI: 10.3390/colloids4010003
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling for Nanofluid Flow: A Stretching Sheet with Thermophysical Property Data

Abstract: This paper reports the use of a numerical solution of nanofluid flow. The boundary layer flow over a stretching sheet in combination of two nanofluids models is studied. The partial differential equation that governs this model was transformed into a nonlinear ordinary differential equation by using similarity variables, and the numerical results were obtained by applying the shooting technique. Copper (Cu) nanoparticles (water-based fluid) were used in this study. This paper presents and discusses all numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…In addition, for all other values of β � 0, 0.2, and 0.4, it is found that the SWCNTs are more efficient, as compared with MWCNTs, with regard to the skin friction coefficient and the Nusselt number. Moreover, these results verified that the skin friction data fit the Weibull distribution, which are found to be in good agreement with results of the previous study [33]. e slip and thermal radiation are also modelled based on the flow and heat enhancement of CNTs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, for all other values of β � 0, 0.2, and 0.4, it is found that the SWCNTs are more efficient, as compared with MWCNTs, with regard to the skin friction coefficient and the Nusselt number. Moreover, these results verified that the skin friction data fit the Weibull distribution, which are found to be in good agreement with results of the previous study [33]. e slip and thermal radiation are also modelled based on the flow and heat enhancement of CNTs.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous industrial and medicinal processes, including medication administration, antibacterial activity, friction reduction, and solar energy absorption, significantly benefit from the movement of nanofluids. Jedi et al 3 have thought of nanofluid flow over the stretched sheet using the shot method (used copper nanomaterials in base liquid). Using the symbolic programming language MATHEMATICA, Das et al 4 addressed the nanofluid flow through the nonlinear permeable stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Sabir et al 35 investigated the solution of singular three‐point second‐order boundary value problems by utilizing novel meta‐heuristic computing solver. The numerical or experimental results with ANN modeling in nanofluids has been examined by the researchers in recent articles 36–40 …”
Section: Introductionmentioning
confidence: 99%